Differential Phospho‐Signatures in Blood Cells Identify LRRK2 G2019S Carriers in Parkinson's Disease. Issue 5 (20th January 2022) - Garrido, Alicia; Santamaría, Enrique; Fernández‐Irigoyen, Joaquín; Soto, Marta; Simonet, Cristina; Fernández, Manel; Obiang, Donina; Tolosa, Eduardo; Martí, María‐José; Padmanabhan, Shalini; Malagelada, Cristina; Ezquerra, Mario; et al.
Abstract: Background: The clinicopathological phenotype of G2019S LRRK2‐associated Parkinson's disease (L2PD) is similar to idiopathic Parkinson's disease (iPD), and G2019S LRRK2 nonmanifesting carriers (L2NMCs) are at increased risk for development of PD. With various therapeutic strategies in the clinical and preclinical pipeline, there is an urgent need to identify biomarkers that can aid early diagnosis and patient enrichment for ongoing and future LRRK2‐targeted trials. Objective: The objective of this work was to investigate differential protein and phospho‐protein changes related to G2019S mutant LRRK2 in peripheral blood mononuclear cells from G2019S L2PD patients and G2019S L2NMCs, identify specific phospho‐protein changes associated with the G2019S mutation and with disease status, and compare findings with patients with iPD. Methods: We performed an unbiased phospho‐proteomic study by isobaric label–based mass spectrometry using peripheral blood mononuclear cell group pools from a LRRK2 cohort from Spain encompassing patients with G2019S L2PD (n = 20), G2019S L2NMCs (n = 20), healthy control subjects (n = 30), patients with iPD (n = 15), patients with R1441G L2PD (n = 5), and R1441G L2NMCs (n = 3) (total N = 93). Results: Comparing G2019S carriers with healthy controls, we identified phospho‐protein changes associated with the G2019S mutation. Moreover, we uncovered a specific G2019S phospho‐signature that changes with disease status and can discriminate patients with G2019S L2PD, G2019S L2NMCs, and healthy controls. Although patients with iPD showed a differential phospho‐proteomic profile, biological enrichment analyses revealed similar changes in deregulated pathways across the three groups. Conclusions: We found a differential phospho‐signature associated with LRRK2 G2019S for which, consistent with disease status, the phospho‐profile from PD at‐risk G2019S L2NMCs was more similar to healthy controls than patients with G2019S L2PD with the manifested disease. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society Abstract :